Er3+ Ions‐Doped Germano‐Gallate Oxyfluoride Glass‐Ceramics Containing BaF2 Nanocrystals. Issue 7 (8th April 2015) - Zhao, Zhiyong; Ai, Bing; Liu, Chao; Yin, Qiaoyun; Xia, Mengling; Zhao, Xiujian; Jiang, Yang; Ballato, J.
<x xml:space="preserve">Abstract</x> Er3+ ions‐doped germano‐gallate oxyfluoride glass‐ceramic containing BaF2 nanocrystals was prepared through conventional melt quenching and subsequent thermal treatment method. X‐ray diffraction patterns and transmission electron microscope images confirmed the formation of BaF2 nanocrystals in glass‐ceramics. Preferential incorporation of Er3+ ions into the BaF2 nanocrystals were confirmed by the absorption spectra and emission spectra, and enhanced upconversion emission and infrared emission were observed. Relatively high transmittance in the mid‐infrared region indicated great potential of this germano‐gallate oxyfluoride glass‐ceramics as host materials for the efficient mid‐infrared emission from rare‐earth ions.